2018
DOI: 10.3390/polym10070727
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Lignocresols from Transgenic and Wild-Type Switchgrass

Abstract: Cafferic acid-O-methyltransferases (COMT) down-regulated transgenic and wild-type switchgrass were separated into lignocresols (LCs) and sugars by a phase separation method involving 72% sulfuric acid and cresol. The isolated LCs were characterized by FTIR, GPC, 1 H NMR and 2D-HSQC to understand potential structural modification caused by transgenic engineering lignin or phase separation treatment. No significant changes were found in terms of molecular weights and the amount of incorporated p-cresols between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this study, we found miR319-PvPCF5 module increased S/G ratio and β-O-4 linkage of switchgrass. A small amount of β-β linkages was also be found in side-chain regions of switchgrass lignin [46]. However, we did not detect any β-β bond in tested DELs, which may be due to different lignin extraction and detection methods [35,46].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In this study, we found miR319-PvPCF5 module increased S/G ratio and β-O-4 linkage of switchgrass. A small amount of β-β linkages was also be found in side-chain regions of switchgrass lignin [46]. However, we did not detect any β-β bond in tested DELs, which may be due to different lignin extraction and detection methods [35,46].…”
Section: Discussionmentioning
confidence: 55%
“…A small amount of β-β linkages was also be found in side-chain regions of switchgrass lignin [46]. However, we did not detect any β-β bond in tested DELs, which may be due to different lignin extraction and detection methods [35,46]. NAC-MYB-based transcriptional regulatory system regulates secondary cell wall biosynthesis and has been well studied in switchgrass [11,13,47,48].…”
Section: Discussionmentioning
confidence: 71%